Endometrial Carcinoma with Peritoneal Inflammatory Nodules Mimicking Peritoneal Carcinomatosis: A Case Report from Bangladesh (Pulse, 2026)
Background: Peritoneal inflammatory nodules are rare, non-neoplastic lesions that can be associated with endometrioid carcinoma of the uterus. Grossly, these lesions may closely resemble peritoneal carcinomatosis, creating significant intra-operative diagnostic dilemmas and risking erroneous upstaging.Case Presentation: We report a case of a 65-year-old postmenopausal woman with endometrioid carcinoma in whom widespread multiple “seedling-like” pelvic peritoneal deposits were observed intra-operatively and were suspicious for advanced disease. Total abdominal hysterectomy with bilateral salpingo-oophorectomy, pelvic lymphadenectomy, and pelvic peritonectomy were performed. Comprehensive Histopathological examination confirmed endometrioid carcinoma with